CONCEPTUAL BASIS OF STRATEGIC GUIDELINES FOR BALANCED REGIONAL DEVELOPMENT OF THE TOURISM INDUSTRY - NOD, Orshoia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
In today’s conditions of global challenges (Russia’s war against Ukraine, the coronavirus pandemic, the economic and energy crisis), the tourism industry is one of the first to experience the most significant negative impact. Recently, the field of tourism and resort-recreation is in a certain decline, due to a decrease in tourist flows, damage to the tourist and resort-recreational infrastructure, and the danger of tourists. In general, under such conditions, the question of developing strategic guidelines for the balanced regional development of the tourism and resort-recreational sphere is acute. The purpose of writing the article is to study the conceptual foundations of strategic guidelines for balanced regional development of the tourism industry. The conceptual foundations of strategic guidelines for balanced regional development of the tourism industry have been studied. The essence of the concept of "balanced development" is summarized. It is emphasized that most scientists consider development as "stable", and "balanced" is an action that characterizes the socio-economic system in the process of its development. It was determined that the balanced development of tourism is a process in which all interested parties interact, taking into account the demand and supply of tourist services, under the conditions of resource conservation for future generations. The main components of balanced regional development of tourism include: socio-cultural, ecological, economic, financial balance, as well as institutional stability. A flowchart of the conceptual foundations of balanced regional development of tourism has been formed, the main part of which is a system of effective management that ensures a positive cultural impact and resource-saving impact on the environment, the result will be socio-economic growth for the region and the country as a whole. The main principles of balanced regional development of the tourism industry have been determined: optimal use of resources, consideration of socio-cultural authenticity of host communities, provision of socio-economic benefits, high level of tourist satisfaction, continuous process of impact monitoring, introduction of necessary preventive and/or corrective measures.